1989
DOI: 10.1002/cne.902860104
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic organization of inputs from the hand to the spinal gray and cuneate nucleus of monkeys with observations on the cuneate nucleus of humans

Abstract: Central termination patterns of primary afferents from the hand and forelimb were studied following subdermal injections of HRP conjugates in macaque monkeys. In the middle layers of the dorsal horn of the spinal cord, afferents from digits 1-5 terminated in a rostrocaudal sequence in separate, elongated columns at cervical levels 5-7. Afferents from the glabrous digits extended to the medial margin of the dorsal gray, while afferents from the dorsal skin of the digits terminated more laterally. Afferents from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 68 publications
3
107
0
Order By: Relevance
“…Neurons responding to stimulation of the lower jaw and neck region have never been reported in V PM (Jones et al, 1986a;Rausell and Jones, 1991a); V PM receives only trigeminal inputs which do not overlap into V PL (Jones et al, 1986b;Rausell and Jones, 1991b). Studies of somatotopy in the dorsal column and principal trigeminal nuclei of monkeys (Kerr et al, 1968;Ferrington et al, 1988;Culbertson and Brushart, 1989;Florence et al, 1989) have not reported whether lower jaw and neck representations are found in both nuclei. There is, however, extensive overlap of upper cervical and trigeminal inputs in the caudal spinal trigeminal nucleus (Kerr, 1972).…”
Section: Intrinsic Connections Of Hand Lower Jaw/neck and Face Reprmentioning
confidence: 99%
“…Neurons responding to stimulation of the lower jaw and neck region have never been reported in V PM (Jones et al, 1986a;Rausell and Jones, 1991a); V PM receives only trigeminal inputs which do not overlap into V PL (Jones et al, 1986b;Rausell and Jones, 1991b). Studies of somatotopy in the dorsal column and principal trigeminal nuclei of monkeys (Kerr et al, 1968;Ferrington et al, 1988;Culbertson and Brushart, 1989;Florence et al, 1989) have not reported whether lower jaw and neck representations are found in both nuclei. There is, however, extensive overlap of upper cervical and trigeminal inputs in the caudal spinal trigeminal nucleus (Kerr, 1972).…”
Section: Intrinsic Connections Of Hand Lower Jaw/neck and Face Reprmentioning
confidence: 99%
“…The central substrates that process these inputs include a substantial portion of the somatosensory area 3b cortex that, in turn, receives driving inputs from subcortical lemniscal substrates (e.g., Jones et al, , 1997Mountcastle, 1984;Florence et al, 1989Florence et al, , 1991Rausell et al, 1992a,b;Jain et al, 1997). These substrates originate in the main cuneate nucleus (CN) and subsequently project to area 3b by means of the ventroposterior lateral nucleus (VPL) of the thalamus.…”
mentioning
confidence: 98%
“…The physiological studies of the Cu in galagos [56] and New and Old World monkeys [57,58,59,60,61,62,63] showed that the cell clusters in the main part of the nucleus (pars rotunda) is related to specific inputs from the hand. These cell clusters, identified as cytochrome oxidase (CO)-patches, receive inputs from digits 1-5 in a lateromedial sequence.…”
Section: Monkeysmentioning
confidence: 99%